Leaf and Stomata Morphometrics of Gayam Inocarpus fagifer (Fabaceae) at Different Altitudes - Smith, Alwi; Sangur, Kristin; Molle, Dessy Fitri; Haurissa, Ludia; Maulany, Grisendy; Renyaan, Belsefren (Jurnal Riset Biologi dan Aplikasinya, 2023)
Gayam (Inocarpus fagifer) is one of the members of the angiosperm flora in Ambon City, Indonesia, that grows and develops at various altitudes. This research aimed to analyze the leaf and stomata morphometrics of these plants in the Aer Louw and Ema Village areas. Leaf samples were taken from the upper, middle, and lower strata and considered as replicates. The morphometric characteristics were measured manually using millimeter block paper and the formula for calculating leaf ratio. Furthermore, the stomata were stained using the direct incision method and safranin. The incision results were analyzed using an Olympus CX23 microscope at 400x magnification. The measurement and observation were analyzed descriptively and correlatively. The results showed that the average leaf width and length, also the midrib length were greater in Aer Louw Village than in Ema Village; while the leaf tip and stalk length were greater in Ema Village than in Aer Louw Village. The characteristics of stomata length and width in Ema Village were greater than in Aer Louw Village; otherwise, the number, index, and density of stomata in Aer Louw Village were greater than in Ema Village. Meanwhile, the correlational analysis showed that the environment influenced the variations of leaves and stomata. Therefore, the variations of leaves and stomata in the areas could predict plant adaptations to different environments.